Prevalence of Peri-implant Disease According to Periodontal Probing Depth and Bleeding on Probing: A Systematic Review and Meta-Analysis - Muñoz, Viviana; Duque, Andres; Giraldo, Astrid; Manrique, Ruben (The International journal of oral and maxillofacial implants, 2018)
To compare changes in the prevalence of peri-implantitis when the unit of analysis is the subject and when the unit of analysis is the implant, by means of meta-analysis with subgroup and sensitivity analyses, according to the case definition and cutoffs. Periodontal probing depth (PPD) and bleeding on probing (BOP) were considered the primary variables. Electronic and manual searches of observational studies of implants with loading of more than 6 months were conducted. The quality of the studies was evaluated, and finally, a description (qualitative analysis) and a meta-analysis (quantitative analysis) of the available studies were performed. Fifty-five studies were included in this systematic review, 32 of which met the criteria for evaluation of disease based on PPD and BOP. A total of 2,734 subjects and 7,849 implants were evaluated. The prevalence of peri-implantitis, defined by PPD and BOP, was 17% when the unit of analysis was the subject, and 11% when it was the implant. If the clinical criterion was PPD ≥ 4 mm, the prevalence by subject was 34% and by implant 11%. If PPD was ≥ 5 mm, the prevalence by subject was 12% and by implant 10%. Finally, if the clinical criterion was PPD ≥ 6 mm, the prevalence by subject was 18% and by implant 10%. The prevalence of peri-implantitis is influenced by the criteria used for the case definition, and the true prevalence may currently be incorrectly estimated.